Apoptotic ablation of platelets reduces atherosclerosis in mice with diabetes - Lee, Man K.S. (Arterioscler Thromb Vasc Biol, 2021)
OBJECTIVE: People with diabetes are at a significantly higher risk of cardiovascular disease, in part, due to accelerated atherosclerosis. Diabetic subjects have increased number of platelets that are activated, more reactive, and respond sub-optimally to anti-platelet therapies. We hypothesized that reducing platelet numbers by inducing their premature apoptotic death would decrease atherosclerosis. APPROACH AND RESULTS: This was achieved by targeting the anti-apoptotic protein Bcl-x(L) (which is essential for platelet viability) via distinct genetic and pharmacological approaches. In the former, we transplanted bone marrow (BM) from mice carrying the Tyr15 to Cys loss of function allele of Bcl-x (known as Bcl-x(Plt20)) or wild-type littermate controls into atherosclerotic prone Ldlr(+/−) mice made diabetic with Streptozotocin (STZ) and fed a Western diet. Reduced Bcl-x(L) function in hematopoietic cells significantly decreased platelet numbers, exclusive of other hematological changes. This led to a significant reduction in atherosclerotic lesion formation in Bcl-x(Plt20) BM transplanted Ldlr(+/−) mice. To assess the potential therapeutic relevance of reducing platelets in atherosclerosis, we next targeted Bcl-x(L) with a pharmacological strategy. This was achieved by low-dose administration of the BH-3 mimetic, ABT-737 tri-weekly, in diabetic Apoe(−/−) mice for the final 6 weeks of a 12-week study. ABT-737 normalized platelet numbers along with platelet and leukocyte activation to that of non-diabetic controls, significantly reducing atherosclerosis, whilst promoting a more stable plaque phenotype. CONCLUSION: These studies suggest that selectively reducing circulating platelets, by targeting Bcl-x(L) to promote platelet apoptosis, can reduce atherosclerosis and lower cardiovascular disease risk in diabetes.